Implementation of Science Learning in Forming Awareness of Environmental Care among Elementary School Students - Listyowati, Enik; Prahani, Binar Kurnia; Gunansyah, Ganes; Hendratno, Hendratno; Istiq'faroh, Nurul (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This study aims to determine the implementation of science learning in forming the awareness of environmental love among grade V elementary school students at SD N 118 Gresik. The method used in this study is qualitative descriptive with source triangulation through observation and documentation and method triangulation through Focus Group Discussion (FGD), carried out on 20 students and homeroom teachers of grade V of SD Negeri 118 Gresik during science learning. The data analysis method goes through several stages: data reduction, data presentation, conclusion, and data verification. The study results showed that the science learning of the material "Humans and Waste" at SD Negeri 118 Gresik gave students an understanding of the types of waste, its impact on the environment, and the importance of waste management through discussions and presentations. Although students show enthusiasm, maintaining environmental cleanliness has not been fully internalized in daily practice, especially in applying the 3R (Reduce, Reuse, Recycle) principle. It appears that science learning has successfully formed the awareness of environmental love among students in class V of SDN 118 Gresik.